Deciphering the interplay among genotype, maturity stage and low-temperature storage on phytochemical composition and transcript levels of enzymatic antioxidants in Prunus persica fruit - Manganaris, George A.; Drogoudi, Pavlina D.; Goulas, Vlasios; Tanou, Georgia; Georgiadou, Egli C.; Pantelidis, Georgios E.; Paschalidis, Konstantinos A.; Fotopoulos, Vasileios; Manganaris, Athanasios G. (My University, 2017)
The aim of this study was to understand the antioxidant metabolic changes of peach (cvs. ‘Royal Glory’, ‘Red Haven’ and ‘Sun Cloud’) and nectarine fruits (cv. ‘Big Top’) exposed to different combinations of low-temperature storage (0, 2, 4 weeks storage at 0 °C, 90% R.H.) and additional ripening at room temperature (1, 3 and 5 d, shelf life, 20 °C) with an array of analytical, biochemical and molecular approaches. Initially, harvested fruit of the examined cultivars were segregated non-destructively at advanced and less pronounced maturity stages and qualitative traits, physiological parameters, phytochemical composition and antioxidant capacity were determined. ‘Big Top’ and ‘Royal Glory’ fruits were characterized by slower softening rate and less pronounced ripening-related alterations. The coupling of HPLC fingerprints, consisted of 7 phenolic compounds (chlorogenic, neochlorogenic acid, catechin, epicatechin, rutin, quecetin-3-O-glucoside, procyanidin B1) and spectrophotometric methods disclosed a great impact of genotype on peach bioactive composition, with ‘Sun Cloud’ generally displaying the highest contents. Maturity stage at harvest did not seem to affect fruit phenolic composition and no general guidelines for the impact of cold storage and shelf-life on individual phenolic compounds can be extrapolated. Subsequently, fruit of less pronounced maturity at harvest were used for further molecular analysis. ‘Sun Cloud’ was proven efficient in protecting plasmid pBR322 DNA against ROO[rad] attack throughout the experimental period and against HO[rad] attack after 2 and 4 weeks of cold storage. Interestingly, a general down-regulation of key genes implicated in the antioxidant apparatus with the prolongation of storage period was recorded; this was more evident for CAT, cAPX, Cu/ZnSOD2, perAPX3 and GPX8 genes. Higher antioxidant capacity of ‘Sun Cloud’ fruit could potentially be linked with compounds other than enzymatic antioxidants that further regulate peach fruit ripening.
Keywords: Antioxidant capacity; Cold storage; DNA oxidation protection; Non-destructive; Peach; Phenolic compounds; Procyanidins